PSYCHOLOGICAL WELL-BEING AS A MEDIATOR IN AUDITOR INSPECTORATE PERFORMANCE ANTECENDENTS - Ribka Shintia Febriarti Bonara; Franco Benony Limba (GEMILANG: Jurnal Manajemen dan Akuntansi, 2023)
This study focuses on the effect of auditor specific experience and compliance pressure on auditor performance in the inspectorate with PWB as a mediating variable for the internal auditors of the inspectorate in Maluku Province, Ambon City, West Seram Regency and Central Maluku Regency. This research is a quantitative research. The sampling technique uses the census sampling method. Data was collected through a survey by distributing questionnaires to 100 research respondents. The method of analyzing data path analysis uses PLS, to measure the direct and indirect effects between Specific Experience and Compliance Pressure on Auditor Performance with PWB as a mediating variable. Based on the test results, it can be confirmed that the three independent variables: Specific Experience, Obedience Pressure and Psychological Well-Being affect Auditor Performance. Likewise with the role of Psychological WellBeing as a mediator in the relationship between the influence of Specific Experience and Compliance Pressure on Auditor Performance.